2023
DOI: 10.3390/ijms24043720
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Expression in Bladder Cancer: A Focused View on Its Diagnostic, Prognostic, and Predictive Role

Abstract: Bladder cancer (BC) is a heterogeneous disease from a molecular, morphological, and clinical standpoint. HER2 is a known oncogene involved in bladder carcinogenesis. Assessing HER2 overexpression as a result of its molecular changes in a routine pathology practice using immunohistochemistry might be a useful adjunct in several scenarios, namely (1) to correctly identify flat urothelial lesions and inverted urothelial lesions in the diagnostic setting; (2) to provide prognostic hints in both non-muscle invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 96 publications
1
5
0
Order By: Relevance
“…Immunoexpression of HER-2 is observed in a subset of sarcomatoid and rhabdoid BUC, although most cases did not harbor HER-2 gene amplification. This data is comparable to what was observed in conventional BUC cases 10 . However, a HER-2 low-content may have impact on the use of new generation drugs which does have effect using the protein bridges of the membranes of neoplastic cells.…”
Section: Discussionsupporting
confidence: 90%
“…Immunoexpression of HER-2 is observed in a subset of sarcomatoid and rhabdoid BUC, although most cases did not harbor HER-2 gene amplification. This data is comparable to what was observed in conventional BUC cases 10 . However, a HER-2 low-content may have impact on the use of new generation drugs which does have effect using the protein bridges of the membranes of neoplastic cells.…”
Section: Discussionsupporting
confidence: 90%
“…HER2 levels are well established to have prognostic value in breast and some gastrointestinal cancers. 83 In bladder cancer, HER2 overexpression strongly correlates with tumor progression and a poor prognosis. 84 The success achieved with HER2-targeted ADCs in other cancers 85 has generated interest to study its potential efficacy in UC, with multiple completed and ongoing trials ( Tables 4 and 5 ).…”
Section: Her2 Targeting Therapiesmentioning
confidence: 99%
“…Some studies have shown that HER2 overexpression is associated with shorter PFS, whereas other studies have shown a more positive prognosis. 83 The Destiny-Pantumor-02 trial suggested that patients with higher levels of HER2 positivity may be associated with a better response to treatment with T-DXd, although patients with low expression may respond as well. 90 While some level of HER2 expression is a prerequisite for treatment with a HER2 ADC, the absolute level of expression may not substantially affect treatment decisions.…”
Section: Biomarkersmentioning
confidence: 99%
“…Globally, bladder cancer is the 7th most common cancer and the 13th most common cause of cancer-related death [1]. Urothelial carcinoma (UC) is the most common histologic type, constituting about 90% of all bladder cancers [2].…”
Section: Introductionmentioning
confidence: 99%